Andrea Hajek, Negotiating Memories of Protest in Western Europe. The Case of Italy, London, Palgrave Macmillan, 2013, pp.232. - Lorenzo Zamponi (Coordinamento SIBA, 2014)
No absrtact is required for book reviews